... And Dignity for All : Unlocking Greatness through Values-Based Leadership - Despain, James; Converse, Jane (Pearson, 2003)
And Dignity for All is about leading with values, leading by example, and - in so doing - unleashing the astonishing commitment and innovation that are buried within your organization right now. Discover how Jim Despain and his colleagues used values-based management to transform Caterpillar's Track-Type Tractors Division into one of the firm's key profit centers. Jim's honesty and ability to rise from the ashes of his mistakes are inspirational. His respect for the common worker and personal search for dignity and self-worth lead him to a new kind of leadership. And his transformation of a struggling organization provides a powerful blueprint for transforming your own - you can make it happen, too.